PENINGKATAN KETERAMPILAN KOMUNIKASI DAN PRESTASI BELAJAR PESERTA DIDIK MELALUI MODEL TEAM GAMES TOURNAMENT MENGGUNAKAN MEDIA KONKRET DI KELAS III SD NEGERI 3 PENGADEGAN - Diah Tri Lutfianti; Arifin Muslim (STKIP Subang, 2024)
Initial observations serve as the basis for the implementation of this research. It was found that the majority of Grade III students at SD N 3 Pengadegan still lack communication skills, and the overall mastery level has not reached the predetermined KKM (Minimum Mastery Criteria), which is 65. This research was conducted using the classroom action research method consisting of two cycles through four stages of each cycle: planning, implementation, observation, and reflection. The subjects of this study were 21 Grade III students of SD N 3 Pengadegan. The research instruments used were observation, evaluation questions, and questionnaires. Data analysis shows that students' communication skills have significantly improved from the beginning (55%) to the end (95%), indicating a significant change in students' communication skills. Additionally, academic achievement also increased from 38.10% to 78.56%, with the overall average scores for each cycle being 60.31 and 76.74, respectively. Therefore, it can be concluded that the implementation of the Team Games Tournament model using concrete media in Grade III of SD N 3 Pengadegan can enhance students' communication skills and academic achievement.